Development of a Python-Based Program for Pareto Analysis in Construction Project Cost Management - Toriq Arif Ghuzdewan (G-Tech: Jurnal Teknologi Terapan, 2025)
Construction projects are highly complex activities that involve various types of tasks with a large number of work items and resources. This complexity makes cost management a significant challenge. To address this challenge, the Pareto principle, which asserts that the majority of results come from a small number of causes, can be applied to focus attention on the most significant tasks. While Pareto analysis can be performed using spreadsheet such as Microsoft Excel, this process often requires lengthy steps, particularly when multiple Pareto charts need to be generated. This study aims to develop a Python-based program that allows for the automatic and efficient generation of Pareto charts. The program was developed through a structured process of identifying requirements, designing, coding, and testing. The program was tested using simulated cost estimate data from a building construction project and the results showed that the program successfully generated Pareto charts for the analysis of labor, material, and overall work-related costs. The testing also indicated that the program is user-friendly, with a step-by-step input mechanism that facilitates ease of use.